2022
DOI: 10.1021/acsanm.2c04681
|View full text |Cite
|
Sign up to set email alerts
|

CdS Nanoparticles Supported on Ti3C2Tx MXene for the Efficient Photocatalytic Production of H2O2: Implications for the Photocatalytic Degradation of Emerging Contaminants

Abstract: Herein, Ti 3 C 2 T x MXene was prepared and used to anchor CdS nanoparticles, and CdS/Ti 3 C 2 T x (CT) photocatalyst with an interfacial Schottky junction was obtained for in situ hydrogen peroxide (H 2 O 2 ) production to degrade emerging contaminants. CT-0.5 photocatalyst had the highest H 2 O 2 production yield, which was 401 μmol L −1 within 1 h in pure water without organic sacrificial reagents under visible-light irradiation (λ > 420 nm), more than 3 times that of pristine CdS. The excellent photocataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 80 publications
0
25
0
Order By: Relevance
“…For n-type semiconductors, the CB potential is usually 0.1 V lower than its flat-band potential, which is equivalent to its Fermi level ( E f ) . Because the ECB and EVB of CdS were calculated to be −0.385 and 1.765 V, respectively, its E f could be estimated to be −0.285 V, which was more negative than the value of −0.08 V of Ti 3 C 2 T x MXene calculated in our previous study . Therefore, when CdS QDs were tightly attached to the Ti 3 C 2 T x MXene surface, a Schottky junction would be formed at the intimate coupling interface, accompanying the VB and CB upward bending of the CdS QDs, as the two different E f ’s must reach a new equilibrium.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…For n-type semiconductors, the CB potential is usually 0.1 V lower than its flat-band potential, which is equivalent to its Fermi level ( E f ) . Because the ECB and EVB of CdS were calculated to be −0.385 and 1.765 V, respectively, its E f could be estimated to be −0.285 V, which was more negative than the value of −0.08 V of Ti 3 C 2 T x MXene calculated in our previous study . Therefore, when CdS QDs were tightly attached to the Ti 3 C 2 T x MXene surface, a Schottky junction would be formed at the intimate coupling interface, accompanying the VB and CB upward bending of the CdS QDs, as the two different E f ’s must reach a new equilibrium.…”
Section: Resultsmentioning
confidence: 59%
“…16 Because the ECB and EVB of CdS were calculated to be −0.385 and 1.765 V, respectively, its E f could be estimated to be −0.285 V, which was more negative than the value of −0.08 V of Ti 3 C 2 T x MXene calculated in our previous study. 69 Therefore, when CdS QDs were tightly attached to the Ti 3 C 2 T x MXene surface, a Schottky junction would be formed at the intimate coupling interface, accompanying the VB and CB upward bending of the CdS QDs, as the two different E f 's must reach a new equilibrium. Under simulated solar irradiation, the CdS QDs catalysts were excited to produce electron−hole (e − −h + ) pairs and then photoinduced e − migrated rapidly from the CB of CdS to Ti 3 C 2 T x MXene through the formed Schottky junctions, while the formed Schottky junctions could also inhibit the recombination of photoinduced electron−hole pairs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In light of these, it can be concluded that the composition and modification on the surface of Mo 2 C MXene can dramatically affect the intrinsic nature of MXene and the final catalytic activity. 44 The energy band structure of a semiconductor is crucial to comprehend the mechanism in photocatalysis for H 2 evolution activity. According to Figure 5a, the band gap energy (E g ) of samples can be obtained by the Tauc plots, in which (αhv) 1/n is plotted versus the photon energy (hv), where α is the absorbance derived from the UV−vis DRS in Figure 5a, n is 1/ 2 because the nature of CdS is a direct band gap material and CdS has a characteristic of n-type semiconductors, 45 and h and v are the Planck constant and irradiation frequency, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It is evident that a lower charge-transfer resistance with the smallest semicircles arc is observed for Mo 2 C MXene with Li + , which is beneficial to the fast migration of photogenerated electrons excited from CdS and thereby the effective suppression of carrier recombination. In light of these, it can be concluded that the composition and modification on the surface of Mo 2 C MXene can dramatically affect the intrinsic nature of MXene and the final catalytic activity …”
Section: Resultsmentioning
confidence: 99%
“…Recent investigation indicates that the removal of Cr(VI) by photocatalytic reduction becomes a promising method to treat the pollution of Cr(VI) due to its distinct advantages, e.g., being fast and eco-friendly, and harnessing solar energy. [21][22][23][24][25][26][27][28][29][30] The prospect of converting sustainable solar energy into clean energy or using solar light to deal with environmental pollutants through photocatalysts has driven the search for efficient photocatalysts. 31 Among the photocatalysts explored, metal-free carbon nitride (CN) has become an extremely attractive visible light photocatalyst due to its environmental friendliness and good stability.…”
Section: Introductionmentioning
confidence: 99%